2008
DOI: 10.1002/dev.20288
|View full text |Cite
|
Sign up to set email alerts
|

Domperidone interferes with conditioned disgust reactions but not taste avoidance evoked by a LiCl‐paired taste in infant rats

Abstract: Rats exhibit taste avoidance and conditioned disgust reactions when stimulated with a tastant paired with lithium chloride (LiCl). Lithium-mediated activation of chemoreceptor nuclei at the brainstem appears to determine the acquisition of conditioned taste aversion (CTA) in adult rodents. Domperidone (DOM), an anti-emetic drug that does not cross the blood-brain barrier, was employed to analyze mechanisms underlying LiCl-mediated CTA in infant rats. On postnatal day 13 animals were given DOM followed by a pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
1
23
1
Order By: Relevance
“…SDS has been proven capable of promoting anti-fatigue, anti-cancer, anti-oxidant and anti-aging effects [25]. Rats have been found to exhibit taste avoidance and conditioned disgust reactions after stimulation with LiCl [26]. Concerning in vivo and in vitro TUNEL experiments, we found that the administration of LiCl improved dopaminergic neuron loss and prevented PC12 cells from apoptosis, and SDS treatment increased the protective effect of LiCl on 6-OHDA-treated PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…SDS has been proven capable of promoting anti-fatigue, anti-cancer, anti-oxidant and anti-aging effects [25]. Rats have been found to exhibit taste avoidance and conditioned disgust reactions after stimulation with LiCl [26]. Concerning in vivo and in vitro TUNEL experiments, we found that the administration of LiCl improved dopaminergic neuron loss and prevented PC12 cells from apoptosis, and SDS treatment increased the protective effect of LiCl on 6-OHDA-treated PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that, in the preweanling rat, ethanol may share some postabsorptive effects with LiCl. Emetic-like effects are critical for the expression of LiCl-mediated disgust reactions in the infant rat (Pautassi et al, 2008a). …”
Section: Conditioned Aversion Mediated By Ethanol In the Preweanlimentioning
confidence: 99%
“…BAC's half-life is approximately 4 hrs following i.p. administration of the drug in rats and it has been shown to become pharmacologically active within 15 min, [2,18]. Thirty min following the injections animals were simultaneously presented with two different bottles of SAC (0.3% and 0.6%, %w/v) for a 30 min period, and bottle switching occurred as described for CS presentation on Day 1, the First Taste Exposure Day.…”
Section: Resultsmentioning
confidence: 99%
“…Lithium chloride was chosen as a comparison measure since it is a more conventional and well-established US found in many other taste aversion studies [15,18-21]. If animals steadily decreased their SAC consumption to nearly zero over the three acquisition trials we could conclude that BAC was acting as an US.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation